Strong positive selection biases identity-by-descent-based inferences of recent demography and population structure in Plasmodium falciparum - Guo, Bing (2024)
Funding Information: We would like to thank the participants in studies contributing clinical samples from which the parasite WGS data were generated, as well as the clinical investigators at the Armed Forces Research Institute of Medical Sciences who conducted the studies contributing parasite isolates to our in-house data set. This publication uses data from the MalariaGEN Consortium and Plasmodium falciparum Community Project as described in “An open data set of Plasmodium falciparum genome variation in 7000 worldwide samples. MalariaGEN et al., Wellcome Open Research 2021642 DOI: 10.12688/wellcomeopenres.16168.1.” This work was supported by NIH 1R01AI145852 granted to ST-H and TDO by the U.S. National Institutes of Health. Publisher Copyright: © The Author(s) 2024.